2014
DOI: 10.1021/jm500175z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Water-Binding Pocket of the Type II Dehydroquinase Enzyme in the Structure-Based Design of Inhibitors

Abstract: Structural and computational studies to explore the WAT1 binding pocket in the structure-based design of inhibitors against the type II dehydroquinase (DHQ2) enzyme are reported. The crystal structures of DHQ2 from M. tuberculosis in complex with four of the reported compounds are described. The electrostatic interaction observed between the guanidinium group of the essential arginine and the carboxylate group of one of the inhibitors in the reported crystal structures supports the recently suggested role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Indeed, E125 interacts with water for <7.0% of the simulation time when εC is bound to AAG (Table S4 and Figure S3). Our new proposal for the role of water reorganization in AAG inhibition complements literature highlighting the diverse function of water in substrate or inhibitor binding for several other enzymes, including kinases, 74 amino acid biosynthetic enzymes, 75 and receptor proteins. 76 Active site water reorganization may also explain AAG inhibition by other pyrimidines, such as 3-methyluracil, 3-methylthymine, and 3ethyluracil, 30 and should be explored further.…”
Section: Despite Similar Active Site Configurations Subtlementioning
confidence: 57%
“…Indeed, E125 interacts with water for <7.0% of the simulation time when εC is bound to AAG (Table S4 and Figure S3). Our new proposal for the role of water reorganization in AAG inhibition complements literature highlighting the diverse function of water in substrate or inhibitor binding for several other enzymes, including kinases, 74 amino acid biosynthetic enzymes, 75 and receptor proteins. 76 Active site water reorganization may also explain AAG inhibition by other pyrimidines, such as 3-methyluracil, 3-methylthymine, and 3ethyluracil, 30 and should be explored further.…”
Section: Despite Similar Active Site Configurations Subtlementioning
confidence: 57%
“…[238][239][240] Recently, several structural and computational studies to explore water-binding pockets have been reported. [241][242][243][244] One way to systematically improve existing weak binders could focus on identifying and later chemically optimizing those moieties with a particular proximity or orientation to water molecules in the protein−binder complex. For example, the X-ray structure of the antiviral drug Arbidol (195) with influenza hemagglutinin revealed a highly ordered water molecule adjacent to Arbidol, and this was exploited in the structure-based design of Arbidol analogues (Figure 32).…”
Section: Exploring Water-binding Pockets (Structural Water Molecules) In Structure-based Designmentioning
confidence: 99%
“…Specifically, the 3-substituted cyclohexene derivatives 31-36, the tetrahydrobenzothiophene derivatives 37, the O-alkyl derivatives 38, and the 2,3-disubstituted compounds 39 were reported ( Fig. 9) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. A summary of the inhibition constants of these compounds against Mt-DHQ2 and Hp-DHQ2 are shown in Tables 1 and 2.…”
Section: Enolate Intermediate Mimeticsmentioning
confidence: 99%
“…For instance, replacement of the ethylene spacer in 36.1 by a propylene one, compound 36.4, leads to a decrease in the inhibition potency by up to 4-fold ( Table 1). Taking into account the important stabilizing contribution that the interaction between WAT1 and either enolate mimetics like compound 38, the natural substrate or the enolate intermediate 32 seem to have in their binding with the DHQ2 enzyme, the WAT1 binding pocket was also explored in the structure-based design of inhibitors of these enzymes [70]. This aspect was explored with compounds 40-43 (Fig.…”
Section: Enolate Intermediate Mimeticsmentioning
confidence: 99%